Bacterial cellulose membrane combined with BMSCs promotes wound healing by activating the notch signaling pathway - Wang, Xiaoyang; Zhao, Jie; Wang, Xiaochuan; Zhang, Jingjuan; Wang, Yi; Wang, Xinyue; Jia, Shanshan; Shi, Nian; Lu, Meiqi; Su, Hongxia; Zhang, Jixun; Jiang, Duyin (Frontiers in Surgery, 2023)
Objective The bacterial cellulose membrane (BCM) has been widely studied and applied as a new biomaterial for wound healing, but causes pain with frequent dressing changes. Local application of bone marrow mesenchymal stem cells (BMSCs) requires a niche. Furthermore, the effect and mechanism of the BCM combined with BMSCs have not been reported. Methods Morphological and chemical identifications of BCMs were investigated by porosity analyses, scanning electron microscopy, and Fourier-transform infrared spectroscopy. Biological wound dressings (BWDs) were prepared by the BCM in combination with BMSCs. The biological effects of BWDs on human dermal fibroblast (HDF) and VEGF-A in human vascular endothelial cells (HuVECs) were detected in vitro, and the effect of BWDs on acute wounds in mice was detected in vivo. Collagen and angiogenesis were evaluated through hematoxylin–eosin staining and Masson staining. The expressions of COL-1 and VEGF-A and the activation of the Notch signaling pathway in vivo and in vitro were detected by quantitative reverse-transcriptase polymerase chain reaction. Results The BCM had a nanoscale structure and provided a partial niche for the survival and proliferation of BMSCs. BWDs were successfully prepared and regulated the biological behaviors of wound healing-related cells in vitro and upregulated the expressions of COL-1 in HDF and VEGF-A in HuVECs. BWDs promoted wound healing by increasing collagen type I synthesis and angiogenesis in acute wounds in mice. Conclusions BWDs prepared by the combination of nanomaterial BCMs and BMSCs facilitated acute wound healing, which may be regulated by activating the Notch signaling pathway.